2015
DOI: 10.3168/jds.2014-8547
|View full text |Cite
|
Sign up to set email alerts
|

The role of solid feed amount and composition and of milk replacer supply in veal calf welfare

Abstract: Diets used in veal production were linked with welfare problems: that is, behavioral and gastrointestinal health disorders. This study aimed to determine how indicators of calf welfare, that is, behavior and some characteristics of the feces reflecting gastrointestinal health status, are affected by (1) different amounts and compositions of solid feed (SF), (2) the addition of ad libitum long straw to a typical veal diet, and (3) milk replacer (MR) being fed via automated milk dispensers (AMD). Two-week-old Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…For example, maize (cob) silage caused fewer lesions than straw at small amounts (250 g/d) and more lesions than straw in larger amounts (500 g/d; Webb et al, 2013). A finding that contradicts the hypothesis that larger amounts of SF lead to more abomasal damage is that provision of straw or hay ad libitum does not exacerbate lesions caused by MR (Webb et al, 2013(Webb et al, , 2015. We may speculate that ad libitum provision allows the individual calf to select a diet that is quantitatively optimal for its body, including its abomasum.…”
Section: Solid Feedmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, maize (cob) silage caused fewer lesions than straw at small amounts (250 g/d) and more lesions than straw in larger amounts (500 g/d; Webb et al, 2013). A finding that contradicts the hypothesis that larger amounts of SF lead to more abomasal damage is that provision of straw or hay ad libitum does not exacerbate lesions caused by MR (Webb et al, 2013(Webb et al, , 2015. We may speculate that ad libitum provision allows the individual calf to select a diet that is quantitatively optimal for its body, including its abomasum.…”
Section: Solid Feedmentioning
confidence: 98%
“…The effects of roughage on abomasal damage are not entirely clear. Studies have generally found that the feeding of straw, a very coarse roughage, exacerbates abomasal lesions (Van der Mei, 1985;Welchman and Baust, 1987;Breukink et al, 1991;Webb et al, 2013), although 5 studies do not support this (Van Putten, 1982;De Wilt, 1985;Veissier et al, 1998;Prevedello et al, 2012;Webb et al, 2015). The order of roughages from least to most deleterious appears to be hay < maize cob silage/beet pulp < lucerne < maize silage < straw (Wensing et al, 1986;Breukink et al, 1991;Mattiello et al, 2002;Räber et al, 2013b;Webb et al, 2013).…”
Section: Solid Feedmentioning
confidence: 99%
“…Intensive feeding regimes, which are used in the specialized modern veal and beef industry in order to maximize production efficiency, are associated with poor ruminal development. The limited amount of solid feed with a low roughage-to-feed concentrate ratio and the resulting insufficient structure in the diet limits natural rumination, which might lead to frustration, initiating stereotype behavior, such as tongue playing, cross-sucking, sucking on the feed trough and coat licking (Leruste et al 2014;Mattiello et al 2002;Webb et al 2015). Therefore, a minimum daily uptake of solid feed of 250 g starting from the age of 8 weeks is compulsory (97/2/EC 1997), in order to improve animal welfare and gastro-intestinal health (Pardon et al 2014;Webb et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a minimum daily uptake of solid feed of 250 g starting from the age of 8 weeks is compulsory (97/2/EC 1997), in order to improve animal welfare and gastro-intestinal health (Pardon et al 2014;Webb et al 2015). However, this small amount of solid feed does not guarantee complete ruminal development (Webb et al 2015). Calves in specialized modern veal and beef industry are still fed intensively with milk replacer and cereals for 4-6 months, with only limited intake of roughage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation